InTRONs in Biotech - Skoko, Natasa (Mol Biotechnol, 2011)
Eukaryotic gene expression relies on several complex molecular machineries that act in a highly coordinated fashion. These machineries govern all the different steps of mRNA maturation, from gene transcription and pre-mRNA processing in the nucleus to the export of the mRNA to the cytoplasm and its translation. In particular, the pre-mRNA splicing process consists in the joining together of sequences (known as “exons”) that have to be differentiated from their intervening sequences commonly referred to as “introns.” The complex required to perform this process is a very dynamic macromolecular ribonucleoprotein assembly that functions as an enzyme, and is called the “spliceosome.” Because of its flexibility, the splicing process represents one of the main mechanisms of qualitative and quantitative regulation of gene expression in eukaryotic genomes. This flexibility is mainly due to the possibility of alternatively recognizing the various exons that are present in a pre-mRNA molecule and therefore enabling the possibility of obtaining multiple transcripts from the same gene. However, regulation of gene expression by the spliceosome is also achieved through its ability to influence many other gene expression steps that include transcription, mRNA export, mRNA stability, and even protein translation. Therefore, from a biotechnological point of view the splicing process can be exploited to improve production strategies and processes of molecules of interest. In this work, we have aimed to provide an overview on how biotechnology applications may benefit from the introduction of introns within a sequence of interest.